Awareness of Myocardial Infarction in Nangarhar Residents: A Community Based Study - Shams, Akmal; Ibrahimi, Ikramullah; Ahmadzai, Hayatullah (Journal of Cardiology and Cardiovascular Medicine, 2024)
Myocardial infarction is the leading cause of morbidity and mortality worldwide. The overall aim of the study was to evaluate community awareness about myocardial infarction. It was a community-based cross-sectional study conducted during one month including both male and female participants aged 18 years and over in Nangarhar province of Afghanistan. The percentage of awareness for risk factors was as follows: Diabetes (56.4%), Hypertension (43.4%), Elderly (42.1%), Obesity (39.8%), Physical inactivity (38.5%), Hyperlipidemia (37.6%), and Family history (33.8%). Furthermore, knowledge about symptoms and signs was as the following: chest pain (67.4%), pain in neck and jaw (57.8%), Dyspnea (50.7%), pain in arms (46.1%), weakness/fainting (40.1%), cold sweats (38.2%), nausea and vomiting (34.5%), anxiety (29.6%), fever (22.7%), hypotension/shock (20.1%), and silent myocardial infarction (11.3%). Moreover, 24% of participants did not know about the prevention strategies for myocardial infarction. Regarding treatment, 80.3% of participants exactly knew to go to the emergency room, 11.9% of participants would intend to go to a general practitioner (GP), 5.6% of participants would ask others for advice on what to do, and 2.2% of participants would wait to see if the symptoms go away spontaneously or if the symptoms were due to other diseases. The current awareness level about myocardial infarction especially atypical symptoms, risk factors, prevention, and treatment strategies in Nangarhar residents was insufficient, especially in females and healthy individuals, and warrants designing and implementing immediate awareness programs in order to avoid delay of treatment-seeking, misbeliefs about the disease and subsequent morbidity and mortality.